Defining leadership roles in the academic context: A Nursing Deans’ Perspective - Alshammari, Farhan (Advances in Social Sciences Research Journal, 2018)
Albeit research on leadership styles of the educational leaders over the years, most had been westernized than in developing countries. As such, there is still a dearth of the literature of leadership styles of the managers in the universities especially localizing the study on the Deans of the College of Nursing in the Kingdom of Saudi Arabia. This study aims to determine the multifactor leadership styles of the Nursing Deans relating to demographics such as gender, age, years of experience, and the country they graduated from. This study employed quantitative correlational where total population of nursing deans was utilized. The researcher used the Multifactor Leadership Questionnaire Form 6-S (MLQ- 6S), with permission. Data analyses were performed using the statistical software, SPSS version 22.0. The results demonstrated that Nursing Deans employed transactional leadership styles (9.71). The data suggests that there is no significant difference in the leadership styles of the nursing deans as to gender(P>.05). Also, age, years of experience and country they graduated from (highest educational attainment) show no significant difference since all F-values were greater than the 0.05 level of significance. Regardless of age, gender, years of experience and country where they graduated from, the Dean of the College of Nursing can give positively impact the quality of education and eventually improve organizational outcomes.